Osmotic dehydration of some agro-food tissue pre-treated by pulsed electric field: Impact of impeller’s Reynolds number on mass transfer and color - E. Amami; L. Khezami; A.B. Jemai; E. Vorobiev (Journal of King Saud University: Engineering Sciences)
Tissues of apple, carrot and banana were pre-treated by pulsed electric field (PEF) and subsequently osmotically dehydrated in an agitated flask at ambient temperature using a 65% sucrose solution as osmotic medium. The effect of stirring intensity was investigated through water loss (WL) and solid gain (SG). Changes in product color were also considered to analyze the impact of the treatment. The impeller’s Reynolds number was used to quantify the agitation. The Reynolds number remained inferior to 300 thus displaying laminar flow regime. Water loss (WL) and solid gain (SG) increase with the increase of Reynolds number. Mass transfer in osmotic dehydration of all three test particles has been studied on the basis of a two-exponential kinetic model. Then, mass transfer coefficients were related to the agitation intensity. This paper shows that the proposed empirical model is able to describe mass transfer phenomena in osmotic dehydration of these tissues. It is also shown that a higher agitation intensity improves both the kinetics of water loss and solid gain.